Ash the blaze dragon - Mara, Maddy (Mara, Maddy. Dragon girls, 2025)
We are Dragon Girls -- hear us roar! Ash is returning to the Magic Forest, with her friends Maya and Eloise. There, they are able to turn into amazing Fire Dragons and use their special powers to protect the creatures there.The Chaos Queen is still determined to take over the forest, no matter the cost. Ash must harness all her bravery to lead a quest into the Fire Realm. If she and her friends don't work quickly, the realm will cool completely -- and be lost forever! -- Back cover.